2017
DOI: 10.2741/s483
|View full text |Cite
|
Sign up to set email alerts
|

mRNA-miRNA integrative analysis of diabetes-induced cardiomyopathy in rats

Abstract: An integrative analysis of miRNA and mRNA expression profiles in left ventricle (LV) of diabetes-induced rats was performed to elucidate the role of miRNAs and their mRNAs target in diabetic cardiomyopathy (DCM). mRNA (GSE4745) and miRNA (GSE44179) datasets were downloaded from Gene Expression Omnibus 2R (GEO2R) and differentially expressed mRNAs and miRNAs were selected. Cardiotoxicity-related mRNAs (n=7) were analyzed by Ingenuity Pathway Analyses 6 (IPA) and regulatory miRNAs (n=639) were identified using T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…In vascular disease, miR-21 knockout exacerbated AngII-induced TAAD formation in mice through the TGF-β pathway (Huang et al, 2018). Several studies have shown that miR-21 expression is upregulated in the ventricles under diabetic conditions (Guo and Nair, 2017;Lopes et al, 2017). In this study, we found that the expression level of miR-21 was upregulated in the heart tissue of diabetic mice and in H9c2 cells treated with high glucose, which was consistent with previous studies (Thum et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…In vascular disease, miR-21 knockout exacerbated AngII-induced TAAD formation in mice through the TGF-β pathway (Huang et al, 2018). Several studies have shown that miR-21 expression is upregulated in the ventricles under diabetic conditions (Guo and Nair, 2017;Lopes et al, 2017). In this study, we found that the expression level of miR-21 was upregulated in the heart tissue of diabetic mice and in H9c2 cells treated with high glucose, which was consistent with previous studies (Thum et al, 2008).…”
Section: Discussionsupporting
confidence: 91%
“…The bioinformatics and proteomics analysis of recent evidence found that miR-29c expression in cardiomyocytes is inversely correlated with GLUT4 expression [74]. The expression of miR-17 was upregulated in diabetic cardiac myopathy [75]. We, therefore, speculated that GLUT4, KLF15, selenoproteins, and IGF-1 might be the key targets of specific miRNAs, including miR-223, miR-133, miR-223-3p, miR-200a-5p, miR-1, miR-133a, miR-133b, miR-150, and may regulate the transport and uptake of glucose in cardiomyocytes.…”
Section: Mirna-regulated Glucose Metabolismmentioning
confidence: 99%